Post-firing perforation on Roman pottery from the civilian settlement of Vindobona - Chinelli, Rita (Rei Cretariae Romanae Fautorum Acta, 2017)
Secondary perforations were found while studying the common ware fired in an oxidizing atmosphere from an excavation (Rennweg 44) in the civilian settlement of Vindobona (Pannonia). It was a rescue excavation, made in the years 1989–1990, not thoroughly following the stratigraphic criteria, and the documentation is rather incomplete.